Unhealthy Partnerships and Public Health: Breaking Free of Industry - Batt, Sharon (The Hastings Center report, 2019)
In the ambitious new book The Perils of Partnership: Industry Influence, Institutional Integrity, and Public Health, Jonathan Marks argues that far too much baggage is being piled on an old workhorse, conflict of interest. It’s an important concept, he asserts, but public-sector actors can transgress their ethical obligations even when their relations with industry don’t create conflicts of interest. Yet policy-makers have been immersed in public-private partnerships for so long that they do not see the broader implications of such relationships. Marks aims to move the discourse from reassuring terms like “engagement” and “inclusiveness” to concepts that capture the problematic side of the liaisons, like “webs of influence” and “agenda distortion.” Above all, he issues a challenge to public health policy-makers: Ditch the comfortable hand-in-hand industry relationships, which prioritize efficacy over ethics, threatening both the public’s health and the integrity of public health institutions. Adopt instead a paradigm that is “mano a mano,” involving tension, struggle, and, at times, direct conflict with private industry.